Microalgae Diversities in Different Depths of Sendang Biru Beach, Malang East Java - Yustika Aulia Rahma; Getrudis Wihelmina; Sugireng Sugireng; Tri Ardiyati (Biotropika: Journal of Tropical Biology, 2020)
Sendang Biru beach is a one of the coastal area located in Sumbermanjing Wetan, Malang, East Java-Indonesia. As a sea tourism, there are another residents activities such as fishing, fish landing and auction in Malang. That activities can caused pollution on the Sendang Biru aquatic environment. The research aim were to describe the water quality of Sendang Biru aquatic environment based on phytoplankton diversity. This research used several data collection techniques, that were microalgae sampling technique and measurement of physical and chemical water quality. Phytoplankton found in Sendang Biru Beach consists of 47 genus that are genus from seven divisions, Bacillariophyta, Chlorophyta, Cyanophyta, Euglenophyta, Dinophyta, Chrysophyta and Charophyta. The most abundant phytoplankton while having the Indeks Nilai Penting (INP) at the edge zone is the genus Oscillatoria sp. (the abundance is 4368000 Ind/L and INP 26,288). In the central and inner zones are both dominated by Coscinodiscus sp. (The abundance of center zone 4992000 Ind/L and INP 30,499; the abundance of inside zone is 9464000 Ind/L and INP 40,773). The level of diversity of phytoplankton in the three area of Sendang Biru beach are 2,297 in the edge zone; 2,37 in the central zone, and 1,8 in the inner zone. The pollution status of Sendang Biru beach can be classified as polluted moderately based on diversity index value on three different zone in the Sendang Biru Beach.